Simmel and Marx: Complementary Relational Approaches to Romantic Love. A Feminist Revisitation - Sabido Ramos, Olga (Simmel Studies)

(untitled) (Edizioni ETS, 2021)
The main purpose of this article is to re-examine the legacy of Marx and Simmel for the study of romantic love from a feminist perspective. I am interested in the relational legacy these two authors provide for the study of the affective sphere. Specifically, I am interested in highlighting how both offer analytical inputs to consider the relationships between love, power, and conflict. I attempt to answer the following questions: What do Marx and Simmel postulate when they talk about love? What is the complementary contribution of their proposals considering recent studies on love from a feminist perspective? While Marx allows us to incorporate the socio-structural and historical level – specifically the material dimension –, Simmel allows us to incorporate the social process and symbolic exchange – specifically the cultural dimension – to think about the affective dimension of social ties and love as social bond. I consider that from this analytical and political perspective, the Marxist-Simmelian legacy provides a thought-provoking program for the relational analysis of affects, emotions and love.